(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
Preterm birth (PB) is one of the leading causes of perinatal morbidity and mortality. Disturbances in vaginal microbiocenosis, including bacterial vaginosis and aerobic vaginitis, play a key role in the pathogenesis of threatened preterm birth. In this study, changes in vaginal microflora, pH of the environment, and the results of liquid cytology were studied using 58 pregnant women as an example. Data on inflammatory changes in the vaginal epithelium and their relationship with microbiological disturbances are presented.